LEGAL ASPECTS OF CONVECTION-BASED MSME B3 WASTE MANAGEMENT VALUES OF LEGAL JUSTICE - Arief Fahrurrozie Hidayat; Endang Sutrisno; Sudarminto Sudarminto (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
Environmental pollution which can result further because in addition to environmental damage it also poses a hazard, namely specifically the presence of known hazardous and toxic waste. in Sukaraos Village, Cikijing District, Majalengka Regency, which can result in B3 waste pollution in its business so this needs attention from the central government and local governments. The author will review this research to find out related to legal studies in B3 waste management to realize legal justice and aspects of law enforcement carried out by the Majalengka Regency Environmental Service. the analysis is qualitative analysis. Majalengka Regency Regent Regulation Number 33 of 2019 related to the management of hazardous and toxic waste does not reflect legal justice for MSME business actors Convection this is due to the absence of obligations from the local government for the allocation of B3 waste management for business actors, difficult permits and management fees waste that is charged to business actors and is expensive. The aspects of law enforcement carried out by the Majalengka Regency Environmental Service are still not effective because there are factors in law enforcement itself, including legal factors, law enforcement factors, facilities factors, community factors and legal culture factors that have not been realized by the community. The conclusion of this study is that the existing regulations in Majalengka Regency and other regulations have not created legal justice for the perpetrators themselves because environmental law enforcement and protection of business actors have not been maximized due to several law enforcement factors that do not run optimally.